Sampling World History Textbooks: A Review Essay - Gosch, Stephen S. (Teaching History: A Journal of Methods, 1989)
Review essay of Anthony Esler. The Human Venture. Vol. I: The Great Enterprise, A World History to 1500. Vol. II: The Globe Encompassed, A World History since 1500. Englewood Cliffs NJ: Prentice-Hall, 1986. Pp. xii, 340; xii, 399. Paper, 25.33 each volume. Instructor’s manual available; William H. McNeill. A History of the Human Community. Second edition. Vol. 1: Prehistory to 1500. Vol. II: 1500 to the Present. Englewood Cliffs NJ: Prentice-Hall, 1987. Pp. xii, 474; xii, 430. paper, 25.00 each volume. Clothbound combined edition, 36.00; Peter N. Stearns. World History: Patterns of Change and Continuity. New York: Harper and Row, 1987. Pp. x, 598. 25.95. Instructor’s manual available. Essay by Stephen S. Gosch of the University of Wisconsin-Eau Claire.